Age and Gender Impact the Measurement of Myocardial Interstitial Fibrosis in a Healthy Adult Chinese Population: A Cardiac Magnetic Resonance Study - Dong, Yang; Yang, Dan; Han, Yuchi; Cheng, Wei; Sun, Jiayu; Wan, Ke; Liu, Hong; Greiser, Andreas; Zhou, Xiaoyue; Chen, Yucheng (Frontiers in Physiology, 2018)
Abstract Background: Diffuse myocardial fibrosis is a common pathological process in many cardiovascular diseases. In order to determine disease, we must have standard normal imaging values. We investigated myocardial interstitial fibrosis of the left ventricle (LV) in a healthy population of Chinese adults and explored the impact of gender, age, and other physiological factors using a T1 mapping technique of cardiac magnetic resonance imaging (CMR). Materials and Methods: We recruited 69 healthy adult Chinese subjects (35 males; age 18–76). LV function and global strain were obtained from functional imaging. T1 mapping was performed using a modified look-locker sequence. Global and segmental native T1 and extracellular volume (ECV) were calculated using dedicated software. Gender, age, and segmental variation of both native myocardial T1 and ECV of the LV were analyzed.. Results: The global myocardial native T1 and ECV of the LV in this Chinese adult healthy population was 1202 ± 45 ms and 27 ± 3% at 3T field strength, respectively. Females had a higher myocardial native T1 and ECV of the LV compared to males (1210(1188-1264) ms vs 1182(1150-1211) ms, P < 0.001; 28 ± 3% vs 26 ± 3%, P = 0.027, respectively). ECV in older group was higher than younger group (27(26-29)% vs 25(24-29), P=0.019). The multi-variate linear regression analysis showed that only gender (Beta=-0.512, P<0.001) was independently related with global native T1 of LV while gender (Beta=-0.278, P=0.017) and age (Beta=0.303, P=0.010) were independently related with global ECV of LV.From the base to apex of the LV, myocardial native T1 (P = 0.020) and ECV (P < 0.001) significantly increased. Within the same slice of the LV, there were significant segmental variations of both myocardial native T1 (P < 0.001) and ECV (P < 0.001) values. Conclusion: Gender and age have significant impacts on the imaging markers of myocardial interstitial fibrosis in healthy adult Chinese volunteers. Segmental variation of myocardial interstitial fibrosis was also observed.